1996
DOI: 10.21273/jashs.121.2.326
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Timing of Potassium Nitrate Spray Applications to `French' Prune Trees

Abstract: During the fruit growing season, April through August 1990, 1991, and 1992, four sprays of 20-22 liters/tree of KNO3 were applied to `French' prune trees (Prunus domestica L. syn. `Petite d'Agen). Spray applications of KNO3 were compared to single annual soil applications of KCl (1.4-2.3 kg/tree) and sprays of urea + KNO3 with respect to leaf K and N, fruit size, drying ratio, and dry yield. Potassium nitrate spra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Spraying with KNO 3 was previously reported to increase fruit size in 'Patharnakh' japanese pear (Gill et al, 2012), and the increase was greatest at a dose of 1.5% KNO 3 . A study of plum trees [Prunus salicina (Southwick et al, 1996)] revealed that there was a correlation among the dry weight, size of fruit, Total sugar = fructose D sorbitol D glucose D sucrose; sweetness value = fructose · 1.75 D glucose · 0.70 D sorbitol · 0.40 D sucrose · 1.00. Vertical bars indicate SE; 1 mgÁg L1 = 1000 ppm.…”
Section: Discussionmentioning
confidence: 99%
“…Spraying with KNO 3 was previously reported to increase fruit size in 'Patharnakh' japanese pear (Gill et al, 2012), and the increase was greatest at a dose of 1.5% KNO 3 . A study of plum trees [Prunus salicina (Southwick et al, 1996)] revealed that there was a correlation among the dry weight, size of fruit, Total sugar = fructose D sorbitol D glucose D sucrose; sweetness value = fructose · 1.75 D glucose · 0.70 D sorbitol · 0.40 D sucrose · 1.00. Vertical bars indicate SE; 1 mgÁg L1 = 1000 ppm.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it controls many enzyme activities in plants by modulating the rate of photosynthesis and increasing the rate of translocation from leaves through the phloem to storage tissue, which leads to improve yield and fruit quality (Saykhul et al, 2013). Furthermore, Southwick et al (1996) reported that the uptake of potassium absorption from the foliar spray might be more predictable and efficient than uptake from the soil, where soil-cation interactions may delay the process.…”
Section: Discussionmentioning
confidence: 99%
“…A 5,000-ppm solution of Rb was applied twice to prune foliage on each spraying date. Based on experience with foliar potassium treatments, 2 sprays of 5,000 ppm should result in greater uptake than a single 10,000-ppm spray (Southwick et al 1995). The solution was applied using a large (>350 L) herbicide sprayer with dual spray guns fitted with fine-spray nozzles.…”
Section: Methodsmentioning
confidence: 99%